Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.14802/jmd.16020
|View full text |Cite
|
Sign up to set email alerts
|

The MMSE and MoCA for Screening Cognitive Impairment in Less Educated Patients with Parkinson’s Disease

Abstract: ObjectiveTo explore whether the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) can be used to screen for dementia or mild cognitive impairment (MCI) in less educated patients with Parkinson’s disease (PD).MethodsWe reviewed the medical records of PD patients who had taken the Korean MMSE (K-MMSE), Korean MoCA (K-MoCA), and comprehensive neuropsychological tests. Predictive values of the K-MMSE and K-MoCA for dementia or MCI were analyzed in groups divided by educational level.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 17 publications
2
41
1
1
Order By: Relevance
“…Several studies have shown that the MOCA has high sensitivity when compared to the several cognitive screening tests available for MCI diagnosis in a number of populations, not only in PD. 9 , 11 , 19 - 21 A systematic review assessing the diagnostic performance of all cognitive tests for detecting of dementia due to several etiologies, including PD, concluded that the MOCA performed better than the other tests in detecting MCI. 20 Another study comparing the usefulness and diagnostic accuracy of the MOCA and the MMSE in diagnosing Alzheimer’s disease and MCI, concluded that the MOCA proved more sensitive and accurate for diagnosing MCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the MOCA has high sensitivity when compared to the several cognitive screening tests available for MCI diagnosis in a number of populations, not only in PD. 9 , 11 , 19 - 21 A systematic review assessing the diagnostic performance of all cognitive tests for detecting of dementia due to several etiologies, including PD, concluded that the MOCA performed better than the other tests in detecting MCI. 20 Another study comparing the usefulness and diagnostic accuracy of the MOCA and the MMSE in diagnosing Alzheimer’s disease and MCI, concluded that the MOCA proved more sensitive and accurate for diagnosing MCI.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other studies which assessed the MOCA in patients with Parkinson’s disease that had a lower educational level. 19 Also, these patients were not assessed for clinical staging. However, the subjects in this study had the disease for more than 60 months, and this enabled accurate diagnosis of parkinsonism etiology.…”
Section: Discussionmentioning
confidence: 99%
“…This is essential for their use because the MMSE and MoCA can be affected by differences in culture and language [ 8 ]. Furthermore, most of the published data for the MMSE or MoCA in patients with PD were obtained from highly educated subjects; however, many Korean PD patients have a low level of education [ 9 ]. Thus, the current study aimed to validate the two MMSE-MoCA conversion tables in Korean patients with PD.…”
mentioning
confidence: 99%
“…PD patients were diagnosed based on the United Kingdom Parkinson’s Disease Society Brain Bank diagnostic criteria and were recruited from March 2016 to February 2018. The inclusion criteria were as follows: 1) age between 20–79 years old, 2) Hoehn and Yahr (H&Y) stage 1–4, 3) presence of wearing-off phenomenon, 4) absence of significant cognitive impairment as determined by a Montreal Cognitive Assessment (MoCA) score ≥ 15 [ 7 ], 5) absence of significant depression as determined by a Geriatric Depression Scale (GDS) score ≤ 24 [ 8 ], and 6) consent to participate in the study. Patients with atypical parkinsonism, including multiple system atrophy, corticobasal syndrome, and progressive supranuclear palsy, were excluded from the study, as were patients who previously experienced side effects due to LCE.…”
Section: Methodsmentioning
confidence: 99%